2017
DOI: 10.1097/prs.0000000000003374
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing Mirror Image Reconstruction in Unilateral Microtia: Customizing Auricular Framework by Application of Three-Dimensional Imaging and Three-Dimensional Printing

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Despite several reports on different models and designs of 3D-printed ear models, 8 9 10 11 12 their clinical application has seldom been introduced as the previously reported 3D-printed scaffolds were difficult for clinical application. Simply designed “identical” ear models can cause difficulties in real operative fields, since the implantation procedure may cause harm to the vascularity of the skin flap by harming the subcutaneous pedicle emphasized for blood supply in Nagata’s method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several reports on different models and designs of 3D-printed ear models, 8 9 10 11 12 their clinical application has seldom been introduced as the previously reported 3D-printed scaffolds were difficult for clinical application. Simply designed “identical” ear models can cause difficulties in real operative fields, since the implantation procedure may cause harm to the vascularity of the skin flap by harming the subcutaneous pedicle emphasized for blood supply in Nagata’s method.…”
Section: Discussionmentioning
confidence: 99%
“…Since most patients have unilateral microtia, a 3D-printed framework could be designed based on the contralateral unaffected ear. Several reports have been published regarding the 3D printing techniques used for ear reconstruction; 8 9 10 11 12 however, most remain at an experimental stage or are focused on developing 3D printing materials.…”
Section: Introductionmentioning
confidence: 99%
“…By augmenting conventional teaching with the use of high-fidelity 3D printed ears, the participants were able to effectively visualize and recreate the individual components for autologous ear reconstruction using the Firmin technique ( Figure 4 ). The use of 3D carved wax models as an adjunct to ear reconstruction teaching and surgical planning has been previously explored by Chen et al ( 29 ), who has more recently used 3D printed ears derived from imaging data to produces templates for intraoperative planning ( 30 , 31 ). 3D printing the ear separated into its component parts in this study, however, enabled participants to hold and compare their carved pieces directly to an ideal design, gaining a better appreciation how the separate components organize into a 3D auricle.…”
Section: Discussionmentioning
confidence: 99%
“…Symmetry and similarity of the left and right auricles play an important role in getting better correction outcome for CAD. Chen et al [11] reported that his team used three-dimensional (3D) technique in surgical reconstruction of unilateral microtia. By using the 3D technique, a mirror-image framework in high precision of normal auricle implant was produced, thus providing a better symmetry and aesthetic plastic effect.…”
Section: Introductionmentioning
confidence: 99%